Distinct response patterns of plants and soil microorganisms to agronomic practices and seasonal variation in a floodplain ecosystem - Yu, Yanyan; Liu, Hao; Zhang, Lanlan; Sun, Zhongjie; Lei, Binghai; Miao, Yuan; Chu, Haiyan; Han, Shijie; Shi, Yu; Zheng, Junqiang (Frontiers in Microbiology, 2023)
Anthropogenic activities are the greatest threats to floodplain ecosystems. A growing body of literature shows that floodplain ecosystems have experienced increased chemical fertilizer and pesticide loads, which will disturb the above and below ground ecosystems. However, we lack knowledge regarding the effects of such human activities on the vegetation and soil microbiomes in these ecosystems. The aim of the present study was to assess the impact of nitrogen fertilizer and glyphosate addition on the structure and function of the vegetation and soil microbiomes (bacteria, fungi, and protists) in a floodplain ecosystem, and to assess the influence of seasonal variation. We identified distinct response mechanisms of plant and microbial communities to the addition of nitrogen fertilizer and glyphosate, and seasonal variation. Nitrogen fertilizer and glyphosate significantly affected plant diversity, aboveground and underground biomass, C and N content, and significantly changed the leaf area and plant stature of dominant plants. However, the addition of nitrogen fertilizer and glyphosate did not significantly affect the diversity and structure of bacterial, fungal, and protist communities. The application of nitrogen fertilizer could improve the negative effects of glyphosate on the functional traits of plant communities. The seasonal variation of floodplain has significantly changed the soil physical, chemical, and biological properties. Our results showed that compared with that in summer, the soil ecosystem multifunctionality of the floodplain ecosystem in autumn was significantly lower. Seasonal variation had a significant effect on plant diversity and functional traits. Moreover, seasonal variation significantly affected the community compositions, diversity and structure of bacteria, fungi, and protists. Seasonal variation had a stronger impact on fungal community assembly than on that of bacteria and protists. In summer, the assembly of fungal community was dominated by deterministic process, while in autumn, it is dominated by stochastic process. In addition, the negative association among bacteria, fungi, and protists has been strengthened in autumn, and formed a more robust network to cope with external changes. These results extended our understanding of the ecological patterns of soil microbiomes in floodplain ecosystems, and provided support for enhancing the ecological barrier function and the service potential of floodplain ecosystems.